Clinical, Molecular, and Epidemiological Analysis of Dengue Cases during a Major Outbreak in the Midwest Region of Minas Gerais, Brazil - Juliana Cristina Duarte Braga; Leandro César da Silva; Jacqueline Domingues Tibúrcio; Mirna de Abreu e Silva; Lailah Horácio Sales Pereira; Karina Rocha Dutra; Jaqueline Maria Siqueira Ferreira; Débora de Oliveira Lopes; Luciana Lara dos Santos (Journal of Tropical Medicine)
This study aims to perform the first molecular and clinical-epidemiological analysis of dengue cases in Divinopolis, MG, Brazil. Data from 4,110 cases of dengue were accessed and 190 clinical samples were collected for molecular analyses. In this study, 2.7% of the men and 3.0% of the women were admitted to hospital. There was no association between gender and hospital admission. The symptoms observed in this study are according to the Health Ministry, but fever was present in 82.2% and not in 100% of cases. The chance of hospital admission was 1.55 higher in patients with any kind of bleeding (334) and 2.4% of individuals without bleeding were also hospitalized due to other warning signs. In the molecular analyses, 23% of the samples were positive for DENV. DENV-2 and DENV-3 were identified in 2010, DENV-3 in 2011, DENV-1 in 2012, and DENV-1 and DENV-4 in 2013. DENV detection was possible in samples with only one day of symptoms. This first report of dengue data in Divinópolis provided more insight into the viral types and effects of disease in the city, confirming the need for caution in assessing cases of suspected dengue and for revision of the criteria proposed by the Health Ministry to classify cases of the disease.